42nd AIAA Thermophysics Conference 2011
DOI: 10.2514/6.2011-3323
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Layer Transition Flight Experiment Overview

Abstract: In support of the Boundary Layer Transition Flight Experiment (BLT FE) Project, a manufactured protuberance tile was installed on the port wing of Space Shuttle Orbiter Discovery for STS-119, STS-128, STS-131 and STS-133 as well as Space Shuttle Endeavour for STS-134. Additional instrumentation was installed in order to obtain more spatially resolved measurements downstream of the protuberance. This paper provides an overview of the BLT FE Project with emphasis on the STS-131 and STS-133 results. A high-level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Lack of quality flight data to calibrate and quantify the uncertainties with a boundary layer transition assessment tool resulted in an unprecedented and risky spacewalk during STS-114 to repair observed tile damage [42][43]. To lower risk posture for future flights, quantitative IR based global temperature measurements with adequate spatial resolution and dynamic range were proposed to non-intrusively complement the limited thermocouple coverage on the Orbiter [44][45]. Over a period of approximately the next 2.5 years, seven distinct infrared observations of the reentering Orbiter, spanning a Mach range from 6.2 to 18.1, were made.…”
Section: Thermal Imaging (Shuttle Orbiter)mentioning
confidence: 99%
“…Lack of quality flight data to calibrate and quantify the uncertainties with a boundary layer transition assessment tool resulted in an unprecedented and risky spacewalk during STS-114 to repair observed tile damage [42][43]. To lower risk posture for future flights, quantitative IR based global temperature measurements with adequate spatial resolution and dynamic range were proposed to non-intrusively complement the limited thermocouple coverage on the Orbiter [44][45]. Over a period of approximately the next 2.5 years, seven distinct infrared observations of the reentering Orbiter, spanning a Mach range from 6.2 to 18.1, were made.…”
Section: Thermal Imaging (Shuttle Orbiter)mentioning
confidence: 99%
“…Details of the BLT FE program, including discussion of these discrepancies and mitigation strategies, can be found in Ref. 27. These anomalies point to the need for careful calibration of all instrumentation.…”
Section: Shuttle Blt Flight Experiments 2006mentioning
confidence: 99%
“…Thus, for the Boundary Layer Transition Flight Experiment (BLT FE) Project, a manufactured protuberance tile was installed on the port wing of Discovery on STS-119, STS-128, STS-131 and STS-133 and of Endeavour for STS-134. 27 An incremental approach was utilized to increase the protuberance height after successful missions. STS-119 flew a 0.25-inch protuberance with a predicted BLT onset at Comparisons of analytical predictions to the obtained flight data have shown that while BLT onset times have been accurately predicted using BLT Tool Version 2, predicted temperatures are significantly higher than measured, especially at higher Mach numbers.…”
Section: Shuttle Blt Flight Experiments 2006mentioning
confidence: 99%
“…An assessment of the collected data, using the digital NIR imaging sensor, for STS-119, STS-125, STS-128, STS-131, STS-132, STS-133, and STS-134 missions, is presented. A majority of these missions contained a detailed test objective (DTO) to study boundary layer transition (BLT) [11]. The DTO BLT mission flew a modified tile with a protuberance to induce turbulent flow.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a digital NIR imaging system was implemented after a series of rigorous testing at the Solar Tower Thermal Test Facility at Sandia National Laboratories [6,7]. Implementation of the digital NIR camera system has resulted in NIR imagery with improved dynamic range, instantaneous field of view, and signal to noise [8][9][10][11]. The characterizations performed on the digital NIR system included radiometric, spatial, and spectral measurements using blackbody radiation sources and known targets [12,13].…”
Section: Introductionmentioning
confidence: 99%